2009
DOI: 10.1016/s0929-6646(09)60081-4
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Changes in Knowledge and Stigmatization Following Tuberculosis Training Workshops in Taiwan

Abstract: Training workshops in TB control were effective for promotion of knowledge and elimination of stigmatization in first-line caregivers. DOTS workers attached less stigma to TB patients than public health workers, and older workers who had been volunteers attached the least stigma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
33
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 13 publications
4
33
0
2
Order By: Relevance
“…Similarly, study carried out in public health workers and DOTS workers by PS et al, [10] and among high school children by Gopichandran et al, [11] found statistically signifi cant improvement in knowledge regarding tuberculosis from pre-test to post-test.…”
Section: Discussionmentioning
confidence: 83%
“…Similarly, study carried out in public health workers and DOTS workers by PS et al, [10] and among high school children by Gopichandran et al, [11] found statistically signifi cant improvement in knowledge regarding tuberculosis from pre-test to post-test.…”
Section: Discussionmentioning
confidence: 83%
“…Studies have shown that these factors affect the outcomes of TB treatments. Karim et al in Bangladesh and Salami and Olubayo in Ilorin Nigeria reported that male were less likely to adhere to treatment leading to poorer outcomes [23,24]. Similarly, the study of WU et al in Taiwan and a case control study in China by Ai et al revealed that elderly patients and those above 60 years had poorer treatment outcomes respectively [25,26].…”
Section: Discussionmentioning
confidence: 97%
“…23 Also, health workers' TB knowledge improved and stigma was eliminated after a training workshop. 24 However, no prior studies have evaluated knowledge gains after using CVs to communicate TB information. This study showed that using CVs as health educators improved overall knowledge of and attitude toward TB.…”
Section: Discussionmentioning
confidence: 99%